Measurement of global mechanical properties of human thorax: Costal cartilage. (September 2022) - Gradischar, Andreas; Lebschy, Carola; Krach, Wolfgang; Krall, Marcell; Fediuk, Melanie; Gieringer, Anja; Smolle-Jüttner, Freyja; Hammer, Niels; Beyer, Benoît; Smolle, Josef; Schäfer, Ute
Abstract: Surgical resection of chest wall tumours may lead to a loss of ribcage stability and requires reconstruction to allow for physical thorax functioning. When titanium implants are used especially for larger, lateral defects, they tend to break. Implant failures are mainly due to specific mechanical requirements for chest-wall reconstruction which must mimic the physiological properties and which are not yet met by available implants. In order to develop new implants, the mechanical characteristics of ribs, joints and cartilages are investigated. Rib loading is highly dependent on the global thorax kinematics, making implant development substantially challenging. Costal cartilage contributes vastly to the entire thorax load-deformation behaviour, and also to rib loading patterns. Computational models of the thoracic cage require mechanical properties on the global stiffness, to simulate rib kinematics and evaluate stresses in the ribs and costal cartilage. In this study the mechanical stiffness of human costal cartilage is assessed with bending, torsion and tensile tests. The elastic moduli for the bending in four major directions ranged from 2.2 to 60.8 MPa, shear moduli ranged from 5.7 to 24.7 MPa for torsion, and tensile elastic moduli ranging from 5.6 to 29.6 MPa. This article provides mechanical properties for costal cartilage. The results of these measurements are used for the development of a whole thorax finite element model to investigate ribcage biomechanics and subsequently to design improved rib implants.